2007
DOI: 10.3310/hta11460
|View full text |Cite
|
Sign up to set email alerts
|

Drug-eluting stents: a systematic review and economic evaluation

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 40 publications
(92 reference statements)
3
52
0
6
Order By: Relevance
“…Periprocedural MI in our trial was 10% and it was consistent with the data of other trials with 7-10% periprocedural MI [7,21] . Adverse cardiac events frequency was not different between BMS and DES groups, similar to the published data [25] . Researchers investigated the relationship between adverse cardiac events and inflammation and myonecrosis levels postprocedurely [26,27] .…”
Section: Discussionsupporting
confidence: 80%
“…Periprocedural MI in our trial was 10% and it was consistent with the data of other trials with 7-10% periprocedural MI [7,21] . Adverse cardiac events frequency was not different between BMS and DES groups, similar to the published data [25] . Researchers investigated the relationship between adverse cardiac events and inflammation and myonecrosis levels postprocedurely [26,27] .…”
Section: Discussionsupporting
confidence: 80%
“…Recently, several health technology assessments have concluded that DES should be reserved for select patient subsets such as patients with diabetes mellitus or those with long lesions or small vessels. 10,11 However, these findings were based largely on a combination of expert opinion and decision-analytic models without external validation. 12,13 In January 2007, the US Food and Drug Administration responded to emerging safety concerns regarding DES with an advisory statement that cautioned against their use in patients with unapproved or untested indications.…”
Section: Clinical Perspective On P 1037mentioning
confidence: 99%
“…In short, in relation to the use of DES, it is widely www.intechopen.com Coronary Artery Disease -Current Concepts in Epidemiology, Pathophysiology, Diagnostics and Treatment 206 acknowledged that its cost is the true limiting factor; for example, in our area the price of DES is 60-80% higher than conventional stents. Although many studies concluded that DES may be cost effective in large subgroups of patients, under real conditions, the DES costeffectiveness do not come out favorably compared to BMS (Neyt M et al 2009;Hill RA et al 2007;Kuukasjärvi P et al, 2007). …”
Section: Discussionmentioning
confidence: 99%